1999
DOI: 10.1111/j.1728-4457.1999.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bangladesh Fertility Decline: An Interpretation

Abstract: The claim has been made, notably in a 1994 World Bank report, that the Bangladesh fertility decline shows that efficient national family planning programs can achieve major fertility declines even in countries that are very poor, and even if females have a low status and significant socioeconomic change has not occurred. This article challenges this claim on the grounds that Bangladesh did experience major social and economic change, real and perceived, over the last two decades. This proposition is supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…Table 2.1 summarises some of the key changes over the last three decades. NIPORT et al (2009) The rapid achievement of lower fertility rates in Bangladesh (see Table 2.2) owes to a combination of access to and latent demand for fertility control services (Simmons 1996;Caldwell et al 1999;Kabeer 2001a). With respect to maternal mortality, deaths per 100,000 live births more than halved in the 15 year period up to 2001 (Table 2.1), although they remain high (Annex Table A.1).…”
Section: Human Development (Health and Education)mentioning
confidence: 99%
“…Table 2.1 summarises some of the key changes over the last three decades. NIPORT et al (2009) The rapid achievement of lower fertility rates in Bangladesh (see Table 2.2) owes to a combination of access to and latent demand for fertility control services (Simmons 1996;Caldwell et al 1999;Kabeer 2001a). With respect to maternal mortality, deaths per 100,000 live births more than halved in the 15 year period up to 2001 (Table 2.1), although they remain high (Annex Table A.1).…”
Section: Human Development (Health and Education)mentioning
confidence: 99%
“…For instance, Caldwell et al express doubt that the Bangladesh family planning program could have reduced the TFR by approximately three births per woman over two decades in the absence of significant social change. 10 The same controversy exists regarding the fertility decline in the developing world in general. Robey et al argue that family planning has the most direct influence on fertility.…”
mentioning
confidence: 99%
“…Therefore, large mean land holding women had less preferred to decide to use family planning methods. Caldwell et al [19] reported that in Thailand smaller land sizes have facilitated the adoption of contraceptive methods implying that there is some relationship between land size and contraceptive use. Maglad [20] concluded in his study on effect land size on fertility in rural Sudan that the land size is negatively related with the use of birth control methods.…”
Section: The Descriptive Statistics Results Of Explanatory Variablesmentioning
confidence: 99%